Seroprevalence of varicella-zoster virus among pregnant women in Fayoum Governorate, Egypt - Enas G. Ibrahim; Wafaa Y. Abdel Wahed; Hanaa M. Eid; Wessam S. Deeb (SpringerOpen, 2019)
Abstract Background Chickenpox infection acquired during pregnancy is a serious condition. There may be congenital malformations and neonatal varicella syndrome with significant morbidity and mortality. Egypt has no routine varicella-zoster vaccination program. Objective To assess the immune status against varicella-zoster virus (VZV) antibodies among a group of pregnant women and to study the relationship between VZV seroprevalence and some sociodemographic characteristics. Subjects and methods A descriptive cross-sectional study was conducted on a group of pregnant women (n = 333) attending antenatal care (ANC) clinic at Fayoum University Hospital. Serologic testing for VZV was performed using ELISA through the years 2016-2017. Results VZV seroprevalence was detected in 294 (88.3%) of the 333 recruited pregnant women. Older age > 25 years old was significantly associated with low percent of VZV-negative antibodies (6.7% in versus 17.4% in younger age, OR (95%CI) 0.34 (0.17-0.70)), also having more than one child was significantly associated with a low percent of VZV-negative antibodies (8.2% versus 16.1% among participants with no children or having one child, OR 0.34 (0.17-0.70)). Conclusions Despite the absence of a routine VZV vaccination program in Egypt, VZV immunity was high among pregnant women, but less than that reported in many developed countries. We recommend targeted vaccination for women in the reproductive age especially young and primipara. Trial registration Ethical Committee Registration number R67 session 42: date 12/11/2017(retrospectively registered).